ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN KERIPIK TEMPE DI SENTRA OLEH-OLEH KEDUNG JENAR, KABUPATEN BLORA - Destisya Firsty Bianridha; Agus Setiadi; Suryani Nurfadillah (Universitas Galuh, 2022)
Tempe chips are processed soybean products that are consumed as a snack which has a high demand in the community, especially in Blora Regency. The demand for tempe chips is influenced by several factors, including the price of tempe chips, the price of onion chips, the price of banana midrib chips, age, consumer income, number of family members, consumer tastes, and time of purchase. This study aimed to analyze the factors that influence the demand for tempe chips and to analyze the elasticity of demand for tempe chips at the Kedung Jenar Tempe Chips Center, Blora Regency. The research location was selected by purposive sampling. The method used is survey method and using 100 respondents. Determination of respondents used accidental sampling. Data were analyzed by multiple linear regression. The results of multiple linear regression analysis show that the independent variables simultaneously had a significant effect on the dependent variable. Partially, the price of tempe chips, the price of onion chips, age, consumer income, number of family members, consumer tastes, and time of purchase affected the demand for tempe chips. While the price of banana midrib chips had no effect on the demand for tempe chips. The price elasticity of tempe chips was 0.371 inelastic so it is included in the category of normal goods. Cross elasticity with onion chips had an elasticity of 0,258 and banana midrib chips had an elasticity of 0.473 as substitutes. The income elasticity was 0.76.